2018
DOI: 10.1088/2399-1984/aaa068
|View full text |Cite
|
Sign up to set email alerts
|

Rapid shear alignment of sub-10 nm cylinder-forming block copolymer films based on thermal expansion mismatch

Abstract: Directed self-assembly of block copolymers (BCPs) provided by shear-stress can produce aligned sub-10 nm structures over large areas for applications in integrated circuits, next-generation data storage, and plasmonic structures. In this work, we present a fast, versatile BCP shear-alignment process based on coefficient of thermal expansion mismatch of the BCP film, a rigid top coat and a substrate. Monolayer and bilayer cylindrical microdomains of poly(styrene-b-dimethylsiloxane) aligned preferentially in-pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…317 A similar microstructure comprising sub-10 nm cylindrical microdomains of PS-b-PDMS BCP aligned in preferential directions, was also obtained by shearing, at a high temperature, cracked pieces of SiO 2 previously coated on top of the BCP. 318 The efficiency of film alignment via mechanical shearing can be increased by combining the latter with SVA. 319,320 Qiang and co-workers applied this approach to deliver unidirectionally aligned cylindrical nanostructures of a variety of BCP systems, including PS-b-PB-b-PS, PS-b-PDMS, PS-b-P2VP or PSb-polyisoprene-b-PS (SIS).…”
Section: -Published By the Royal Society Of Chemistrymentioning
confidence: 99%
“…317 A similar microstructure comprising sub-10 nm cylindrical microdomains of PS-b-PDMS BCP aligned in preferential directions, was also obtained by shearing, at a high temperature, cracked pieces of SiO 2 previously coated on top of the BCP. 318 The efficiency of film alignment via mechanical shearing can be increased by combining the latter with SVA. 319,320 Qiang and co-workers applied this approach to deliver unidirectionally aligned cylindrical nanostructures of a variety of BCP systems, including PS-b-PB-b-PS, PS-b-PDMS, PS-b-P2VP or PSb-polyisoprene-b-PS (SIS).…”
Section: -Published By the Royal Society Of Chemistrymentioning
confidence: 99%
“…Berggren et al found that a thermally induced shear stress created through differences in thermal expansion of a BCP film, the substrate, and a rigid inorganic topcoat, could successfully orient domains of the BCP. [381] This was accomplished by controllably cracking an SiO 2 topcoat on the surface of a PS-b-PDMS film which resulted in rapid ordering of the cylindrical structures in less than a minute of processing time. Importantly, these combinations of techniques could provide highly valuable insight into the development of practices to fabricate highly aligned BCP structures.…”
Section: Combined Techniques For Bcp Alignmentmentioning
confidence: 99%
“…The main application of PDMS-containing BCPs is to use them as precursors to prepare nanoporous materials including monoliths and thin films or membranes by converting some discrete components in the phase-separated BCPs into voids . The phase separation behaviors of PDMS-containing BCPs can be regulated to produce diverse morphologies such as cylinders oriented in the perpendicular or parallel direction. The phase-separated BCPs are then used to generate arrays of discrete nano-objects or nanoporous scaffolds by selective removal of the PDMS blocks or all of the organic moieties in the BCPs. , Some researchers selectively etched away the PDMS domains by soaking in hydrofluoric acid (HF), and the continuous phases composed of non-PDMS blocks, typically PS, cross-linked PB, or PI are left behind, producing nanoporous films or monoliths with interconnected porosities initially occupied by the PDMS phases (Figure a). Alternatively, some others prefer to use plasma treatment to decompose the PS blocks and the organic moieties in the PDMS blocks, thus producing nanoporous silicon oxide or silicon oxycarbide (Figure b). However, removal of the PDMS blocks from the BCPs requires harsh conditions, for instance, highly toxic HF and high-energy plasma etching, making the pore-forming process tedious, complicated, and less efficient. Even worse, the pores are produced at the expense of the degradation of PDMS or its organic moieties, which not only weakens the mechanical robustness of the eventually produced porous materials but also results in troublesome byproducts.…”
Section: Introductionmentioning
confidence: 99%